2010
DOI: 10.17221/2995-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating cranial injury due to gunshot in a dog: a case report

Abstract: A ten-month old, male Black and Tan Coonhound dog was referred with ocular bleeding due to gunshot injury. His mental state was normal. A computed tomography revealed that the bullet was planted in the left cranium. It was presumed that the trajectory of the bullet penetrated from the right medial angle of the eye to the orbit, and changed its track to caudo-dorsal by penetrating the cranium, ending up at the left cranium. The bullet was removed by lateral rostrotentorial craniectomy. No complications were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Some literature stated that, gunshot induced penetrating head injuries proceed high mortality in dogs and humans with some obvious signs like as contra-lateral blindness, facial paralysis, seizure, drooping head etc. 8,18,19 In the current case, two bullets that were entered through forehead and embedded in the frontal sinus, was the probable cause of blindness of the left eye. Although, there was no external bleeding however internal bleeding along with blood and blood clots were revealed in postmortem examination.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Some literature stated that, gunshot induced penetrating head injuries proceed high mortality in dogs and humans with some obvious signs like as contra-lateral blindness, facial paralysis, seizure, drooping head etc. 8,18,19 In the current case, two bullets that were entered through forehead and embedded in the frontal sinus, was the probable cause of blindness of the left eye. Although, there was no external bleeding however internal bleeding along with blood and blood clots were revealed in postmortem examination.…”
Section: Discussionmentioning
confidence: 68%
“…5 Some cases reported that animals got survived due to early diagnosis, proper treatment and less severity of injury. [7][8][9][10] Gunshot wounds require the surgical treatment to remove the existing bullet as well as necrotic tissues from the animal's body. Antibiotic and antiinflammatory drugs are widely used to treat the gunshot wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grease collar on the wound edges are not visible. The pellet used was of the round shape type and had an average weight of 0.54 g. The 10x pumping result based on the specification of the air rifle used in this research showed that the muzzle velocity (projectile speed as it leaves the barrel) is 715 fps or 218m / s if it is equalised up to 784.8 km / h. The energy generated by the rifle used in this study belongs to the low energy bracket i.e <400J [9]. The kinetic energy of the projectile upon leaving the barrel is 12.83 J or equivalent to 9.42 fpe.…”
Section: Resultsmentioning
confidence: 86%
“…C omputed tomography (CT) is commonly used to evaluate dogs, cats, horses, and other veterinary patients with head trauma . Accidental head trauma due to ballistic injuries is relatively rare in domestic animals but, if it does occur, it is essential to assess the exact shrapnel location, distribution, size, and proximity to structures with vital functions . Radiography is frequently inaccurate for depicting the exact lesion location .…”
Section: Introductionmentioning
confidence: 99%